Strategi Pengembangan Basis Data Perencanaan Tata Ruang - Roos Akbar (The Institute for Research and Community Services, Institut Teknologi Bandung, 2004)
Experience in planning shows that in Indonesia data mainly the digital data are still not considered important at various level of user and producer. As the consequences many planning products are not based on a proper data in terms of availability, reliability, compatibility in Indonesian context about the digital data for planning. This paper aims at proposing a concept and strategies to better develop GIS-based data construction in Indonesia.Keywords: basis data digital, penataan ruang, sistem informasi geografis